Semiotics of Joseph Curtis… A Study in Perspective and Concept - سعدون, نادية هناوي (ALBAHITH ALALAMI, 2016)
Joseph Curtis wrote in his book (Introduction to Semiotics narrative and rhetoric) on the development of a semiotic project in exploring the meaning of communion. The book is rich in theoretical and analytical benefits both in the approach of texts and in the pursuit of letters in search of mechanisms of scriptural and scriptural generation and mechanics in narrative production, especially as the book offers exercises that help to assess the distance separating the narrative spread from the sin of the text, for the semiotics, Refers to the theoretical developments of the science of relations, through the combination of conventional definitions and the representative and comparative limitations, to provide an approach to the application of the semiarithian story of the semantics of the general organization of the sequences .. We will try in this study to monitor the following:The philosophical perspective of semiotic terms.Procedural deliberation of conceptual perspectives.